Pengembangan Video Media Pembelajaran Sejarah untuk Menumbuhkan Minat Belajar Siswa Kelas XI IPS SMA N 1 Lembah Gumanti - Ramadhani, Sonia; Hastuti, Hera (TSAQOFAH, 2025)
History learning at SMA Negeri 1 Lembah Gumanti remains dominated by conventional media, which has been less effective in fostering students’ learning interest. This study aims to develop video-based History learning media to enhance students’ engagement. The research background is rooted in the low learning interest toward History, which is often perceived as boring and unappealing. The method applied was Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The media were designed to present History material in an engaging manner, with trials conducted among students using learning interest questionnaires and observations. The results show that the learning video received positive responses from both teachers and students and proved effective in fostering students’ interest in History learning.